Collapsing glomerulonephritis in a COVID-19 patient. Case report - Palacios-Guillén, Alaciel (2023)
Acute renal injury due to collapsing glomerulonephritis is associated with high morbidity and mortality, requiring chronic dialysis, COVID-19 is one of its causes. A 17-year-old male patient presented with a four-month history of edema, foamy urine and reduction in the urine flow; anasarca was observed at physical examination. Laboratory values showed creatinine 4,2 mg/dl; albumin 1,9 gr/dl; cholesterol and triglycerides were high; proteinuria 6,7 gr/24h: leucocyturia and hematuria with negative urine culture. Serologies for HIV, syphilis and hepatitis were negative. Studies for systemic lupus were negative. An antigenic test for SARS-CoV-2 was positive as well as an IgG. Renal Biopsy showed Focal and Segmental Glomerulosclerosis, Collapsing variant. He received corticosteroids and cyclosporine. Creatinine improved; proteinuria remained >3 gr/24 hours.